CGIAR Research Program on Water, Land and Ecosystems - Plan of Work and Budget 2019 - CGIAR Research Program on Water, Land and Ecosystems (CGIAR Research Program on Water, Land and Ecosystems, 2019)
WLE continued to improve Flagship milestones. The revisions ensure better alignment with the research portfolios, and better reflection of the annual steps towards outcomes. This remains work in progress as flagships move further towards an increasingly explicit outcome focus. Some changes through to 2021 targets are still required, and WLE will finalize this work in 2019.